Partisipasi Gender dalam Pengelolaan Subak Taman Bali, Desa Sidan, Kecamatan Gianyar Kabupaten Gianyar - I DEWA AYU OKA DAMAYANTHI; NI WAYAN SRI ASTITI; IDA AYU LISTIA DEWI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
Gender Participation In The Management of Subak Taman Bali, Sidan Village,Gianyar Sub District, Gianyar Regency One of the efforts made to develop agriculture is to maintain the continuity of subakmanagement carried out by all members. In fact, the push for gender equality influencesagricultural activities, especially the management of the Taman Bali Subak. This studyaims to find out how gender participation is in the management of Subak Taman Bali bylinking it to the allocation of work time for each gender. The results showed that allmembers of Subak Taman Bali participated in the management of subak. Women aremore dominant in organizing ritual activities with a HOK value of 61.1 HOK. Men aremore dominant in activities that require more energy and more knowledge in agriculturesuch as the search and distribution of irrigation water with a HOK value of 10.7 HOK,operation and maintenance of facilities with a HOK value of 134.2 HOK, mobilizationresources and fund extraction with a HOK value of 1.5 HOK, handling disputes orconflicts with a HOK value of 10.7 HOK and innovation adoption activities with aHOK value of 10.7 HOK. Based on the results, it can be seen that women still have lesstime allocation than men do in managing subak and gender inequality still occurs. It isexpected that they should understand more about gender equality so that it does notdifferentiate men and women especially in the field of ability so that each member hasthe same opportunity to be able to participate more in managing the Subak Taman Bali.